(untitled) - Ungson, Gerardo R. (Boston, 1997)
In the 1960s, Korea embarked on an ambitious program of economic development. By the 1980s, the pace of development had accelerated, and Korean companies were beginning to shed their reputation as second-rate, low-tech producers. In the 1990s, strategies of technological and managerial innovation were officially codified by President Kim as Segyehwa, loosely translated as "globalization, " but more generally understood by Koreans as a philosophy and mission to achieve global status in politics, business, education, communications, technology, and the arts. In this book, the authors trace the evolution of Korea's globalization movement and assess the prospects for Korean competitiveness in the future. Despite tremendous advances over the past three decades, Korean enterprises face considerable challenges if they intend to sustain a competitive edge in the global marketplace. The authors identify seven key challenges in the areas of industrial policy, technological innovation, management practice, organizational design, entrepreneurship, and human resource investment. The authors explore the relationships among national culture, management practice, and government policy.
Keywords: Industrial policy,Competition, International,Chính sách công nghiệp,Cạnh tranh, Quốc tế; Korea (South),Nam Hàn (Hàn Quốc)